Core Competencies of Labour Specialist of Social Security Office: Core Competencies of Labour Specialist of Social Security Office - Manosuwankoon, Sutasinee; Tailangka, Wanwipha; Sirivisitkul, Sanit (RATANABUTH JOURNAL, 2023)
The objectives of this research were to study civil servants core competency level in Labour Specialist Position of Social Security Office, and to compare civil servants core competency in Labour Specialist Position of Social Security Office. Classified by personal characteristics, as survey research. The questionnaire was used as a tool for collecting data. The collecting data from Social Security Office in Labour Affairs for 290 people. Data were analyzed using descriptive statistics were frequency, percentage, mean and standard deviation. And inferential analysis were t-test, F-test and one-way analysis of variance (ANOVA). The results of the research were as follows. The civil servant competency in Labour Specialist Position of Social Security Office, in overall found that it was at a high level ( = 4.30). After considering in aspect found that civil servant in Labour Specialist Position of Social Security Office have highest core competency in adhering to accuracy and ethics, with the average being at the highest level ( = 4.61). Followed by achievement - oriented and good service, with the average being at the high level ( = 4.48). For team work have average at high level ( = 4.21). For accumulation of proficiency in a career have average at high level ( = 4.06), respectively. When comparing civil servants core competency in Labour Specialist Position of Social Security Office, classified by personal characteristics found that civil servant in Labour Specialist Position of Social Security Office with different genders have no difference in core competencies. While civil servant in Labour Specialist Position of Social Security Office with different in ages, levels of education, position levels and working period of time in different position, have different core competencies in significantly different which is in accordance with the assumptions that have been set at the statistical level of .01.